Nasal inhalation of antiviral microparticulate powders to target early infection of upper airways - Sabrina Banella; Eride Quarta; Martina Brandolini; Laura Grumiro; Vittorio Sambri; Giovanna Trevisi; Ruggero Bettini; Paolo Colombo; Francesca Buttini; Fabio Sonvico; Georgeta Caraua; Alessandra Rossi; et al. (Drug Delivery and Translational Research, 2026)

Diospyros kaki leaf polyphenolic extract as a new edible source of anti-glycative agents: bioaccessibility and structure-activity relationship investigation - Giulia Moretto; Raffaella Colombo; Sara Perteghella; Stefano Negri; Hellas Cena; Francesca Alessandra Ambrosio; Stefano Alcaro; Giosuè Costa; Adele Papetti (Food Research International, 2026)

Space capacity-based metric to rank in orbit collision risk - Andrea Muciaccia; Francesca Letizia; Mirko Trisolini; Lorenzo Giudici; Stijn Lemmens; Juan Luis Gonzalo; Camilla Colombo (Advances in Space Research, 2026)

Pigmented corn as a gluten-free source of polyphenols with anti-inflammatory and antioxidant properties in CaCo-2 cells - Stefano Piazza; Corinne Bani; Francesca Colombo; Francesca Mercogliano; Carola Pozzoli; Giulia Martinelli; Katia Petroni; Salvatore Roberto Pilu; Elisa Sonzogni; Marco Fumagalli; Enrico Sangiovanni; Patrizia Restani; et al. (Food Research International, 2024)

Environmental impact of object breakup in medium-Earth orbit - Lorenzo Giudici; Juan Luis Gonzalo; Andrea Muciaccia; Camilla Colombo; Mirko Trisolini; Francesca Letizia (Advances in Space Research, 2024)

Climate-responsive design practices: A transdisciplinary methodology for achieving sustainable development goals in cultural and natural heritage - Elena Lucchi; Francesca Turati; Benedetta Colombo; Eva Schito (Journal of Cleaner Production, 2024)

Reversing the trend of agrobiodiversity decline by co-developing food chains with consumers: A European survey for change - Yuna Chiffoleau; Tara Dourian; Géraldine Enderli; Dalia Mattioni; Grégori Akermann; Allison Loconto; Francesca Galli; Gulyás Emese; Zsófia Perényi; Luca Colombo; Sonia Massari; Dominique Desclaux (Sustainable Production and Consumption, 2024)

Robustness analysis and station-keeping control of an interferometer formation flying mission in low Earth orbit - Cristina Erbeia; Francesca Scala; Camilla Colombo (Advances in Space Research, 2024)

The environmental pollutant BDE-47 modulates immune responses in in vitro and in vivo murine models - Bianca Barletta; Silvia Corinti; Francesca Maranghi; Sabrina Tait; Roberta Tassinari; Andrea Martinelli; Alessandra Longo; Valeria Longo; Paolo Colombo; Gabriella Di Felice; Cinzia Butteroni (Chemosphere, 2024)

Characterization of color, phenolic profile, and antioxidant activity of Italian pigmented rice varieties after different technological treatments - Francesca Colombo; Carola Cappa; Corinne Bani; Marco Magni; Simone Biella; Patrizia Restani; Chiara Di Lorenzo (Food Bioscience, 2023)

Influence of high-pressure homogenization treatments combined with lysozyme activated packaging on microbiological and technological quality of vegetable smoothie during shelf life - Lorenzo Siroli; Virginia Glicerina; Filippo Capelli; Francesca Patrignani; Maurizio Fiorini; Vincenza Andrisano; Matteo Minelli; Matteo Gherardi; Rosalba Lanciotti; Vittorio Colombo; Santina Romani (Food Packaging and Shelf Life, 2023)

Assessing the role of REM13, REM34 and REM46 during the transition to the reproductive phase in Arabidopsis thaliana - Silvia Manrique; Francesca Caselli; Luis Matías-Hernández; Robert G. Franks; Lucia Colombo; Veronica Gregis (Plant Molecular Biology, 2023)
REM (reproductive meristem) transcription factors have been proposed as regulators of plant reproductive development mainly based on their specific expression patterns in reproductive structures, but their roles are still largely unknown probably because of their redundancy. We selected three REM genes ( REM13 , REM34 and REM46 ) for functional analysis, based on their genome position and/or co-expression data. Our results suggest that these genes have a role in flowering time regulation and may modulate cell cycle progression. In addition, protein interaction experiments revealed that REM34 and REM46 interact with each other, suggesting that they might work cooperatively to regulate cell division during inflorescence meristem commitment. Previous attempts of using co-expression data as a guide for functional analysis of REMs were limited by the transcriptomic data available at the time. Our results uncover previously unknown functions of three members of the REM family of Arabidopsis thaliana and open the door to more comprehensive studies of the REM family, where the combination of co-expression analysis followed by functional studies might contribute to uncovering the biological roles of these proteins and the relationship among them.

Manoeuvre planning algorithm for satellite formations using mean relative orbital elements - Alejandro Montero Miñan; Francesca Scala; Camilla Colombo (Advances in Space Research, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The hidden interplay between sex and COVID-19 mortality: the role of cardiovascular calcification - Alberto Cereda; Marco Toselli; Anna Palmisano; Davide Vignale; Riccardo Leone; Valeria Nicoletti; Chiara Gnasso; Antonio Mangieri; Arif Khokhar; Gianluca Campo; Alessandra Scoccia; Matteo Bertini; et al. (GeroScience, 2021)
Recent clinical and demographical studies on COVID-19 patients have demonstrated that men experience worse outcomes than women. However, in most cases, the data were not stratified according to gender, limiting the understanding of the real impact of gender on outcomes. This study aimed to evaluate the disaggregated in-hospital outcomes and explore the possible interactions between gender and cardiovascular calcifications. Data was derived from the sCORE-COVID-19 registry, an Italian multicentre registry that enrolled COVID-19 patients who had undergone a chest computer tomography scan on admission. A total of 1683 hospitalized patients (mean age 67±14 years) were included. Men had a higher prevalence of cardiovascular comorbidities, a higher pneumonia extension, more coronary calcifications (63% vs.50.9%, p<0.001), and a higher coronary calcium score (391±847 vs. 171±479 mm 3 , p <0.001). Men experienced a significantly higher mortality rate (24.4% vs. 17%, p =0.001), but the death event tended to occur earlier in women (15±7 vs. 8±7 days, p = 0.07). Non-survivors had a higher coronary, thoracic aorta, and aortic valve calcium score. Female sex, a known independent predictor of a favorable outcome in SARS-CoV2 infection, was not protective in women with a coronary calcification volume greater than 100 mm 3 . There were significant differences in cardiovascular comorbidities and vascular calcifications between men and women with SARS-CoV2 pneumonia. The differences in outcomes can be at least partially explained by the different cardiovascular profiles. However, women with poor outcomes had the same coronary calcific burden as men. The presumed favorable female sex bias in COVID-19 must therefore be reviewed in the context of comorbidities, especially cardiovascular ones.

Grapes and their derivatives in modulation of cognitive decline: a critical review of epidemiological and randomized-controlled trials in humans - Patrizia Restani; Ursula Fradera; Jean-Claude Ruf; Creina Stockley; Pierre-Louis Teissedre; Simone Biella; Francesca Colombo; Chiara Di Lorenzo (Critical Reviews in Food Science and Nutrition, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Diagnosing acute encephalitis in patients with hematological disorders: caveats and pitfalls - Elisa Vegezzi; Giulia Berzero; Desiree Barbetta; Anna Amelia Colombo; Oscar Borsani; Paolo Bernasconi; Francesca Compagno; Marco Zecca; Giulia Campanini; Anna Simoncelli; Matteo Paoletti; Anna Pichiecchio; et al. (Journal of NeuroVirology, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Trans-splicing of plastid rps12 transcripts, mediated by AtPPR4, is essential for embryo patterning in Arabidopsis thaliana - Luca Tadini; Roberto Ferrari; Marie-Kristin Lehniger; Chiara Mizzotti; Fabio Moratti; Francesca Resentini; Monica Colombo; Alex Costa; Simona Masiero; Paolo Pesaresi (Planta, 2018)

Accessorized DPI: a Shortcut towards Flexibility and Patient Adaptability in Dry Powder Inhalation - Francesca Buttini; James Hannon; Kristi Saavedra; Irene Rossi; Anna Giulia Balducci; Hugh Smyth; Andy Clark; Paolo Colombo (Pharmaceutical Research, 2016)

New Mutations in NEB Gene Discovered by Targeted Next-Generation Sequencing in Nemaline Myopathy Italian Patients - Daniela Piga; Francesca Magri; Dario Ronchi; Stefania Corti; Denise Cassandrini; Eugenio Mercuri; Giorgio Tasca; Enrico Bertini; Fabiana Fattori; Antonio Toscano; Sonia Messina; Isabella Moroni; et al. (Journal of Molecular Neuroscience, 2016)

JC virus urinary excretion and seroprevalence in natalizumab-treated multiple sclerosis patients - Serena Delbue; Francesca Elia; Camilla Carloni; Valentina Pecchenini; Diego Franciotta; Matteo Gastaldi; Elena Colombo; Lucia Signorini; Silvia Carluccio; Anna Bellizzi; Roberto Bergamaschi; Pasquale Ferrante (Journal of NeuroVirology, 2015)

Elevated reinforcing and motivational properties of alcohol at the end of the nocturnal period in sP rats - Paola Maccioni; Irene Lorrai; Maria Francesca Marras; Andrea Contini; Alessandro Capra; Gessica Piras; Pierluigi Caboni; Gian Luigi Gessa; Giancarlo Colombo (Psychopharmacology, 2015)

ER Reorganization is Remarkably Induced in COS-7 Cells Accumulating Transmembrane Protein Receptors Not Competent for Export from the Endoplasmic Reticulum - Massimo D’Agostino; Arianna Crespi; Elena Polishchuk; Serena Generoso; Gianluca Martire; Sara Francesca Colombo; Stefano Bonatti (The Journal of Membrane Biology, 2014)

BbrizAGL6 Is Differentially Expressed During Embryo Sac Formation of Apomictic and Sexual Brachiaria brizantha Plants - Larissa Arrais Guimarães; Diva Maria de A. Dusi; Simona Masiero; Francesca Resentini; Ana Cristina M. M. Gomes; Érica Duarte Silveira; Lilian Hasegawa Florentino; Júlio Carlyle M. Rodrigues; Lucia Colombo; Vera Tavares de C. Carneiro (Plant Molecular Biology Reporter, 2013)

Bisphenol A endocrine disruptor complete degradation using TiO2 photocatalysis with ozone - Alessandra Colombo; Giuseppe Cappelletti; Silvia Ardizzone; Iolanda Biraghi; Claudia L. Bianchi; Daniela Meroni; Carlo Pirola; Francesca Spadavecchia (Environmental Chemistry Letters, 2012)

Pulmonary Spray Dried Powders of Tobramycin Containing Sodium Stearate to Improve Aerosolization Efficiency - Chiara Parlati; Paolo Colombo; Francesca Buttini; Paul M. Young; Handoko Adi; Alaina J. Ammit; Daniela Traini (Pharmaceutical Research, 2009)